Exosome Cargo in Neurodegenerative Diseases: Leveraging Their Intercellular Communication Capabilities for Biomarker Discovery and Therapeutic Delivery - Shuai Zhang; Yu Yang; Xinchen Lv; Xue Zhou; Wangqian Zhao; Linfeng Meng; Shaohua Zhu; Zhixiang Zhang; Ying Wang (Brain Sciences)
The inexorable progression of neurodegenerative diseases (NDs), including Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, and multiple sclerosis, is closely related to irreversible brain decline. Accurately characterizing pathophysiological features and identifying reliable biomarkers for early diagnosis and optimized treatment are critical. Hindered by the blood–brain barrier (BBB), obtaining sensitive monitoring indicators for disease progression and achieving efficient drug delivery remain significant challenges. Exosomes, endogenous nanoscale vesicles that carry key bioactive substances, reflect the intracellular environment and play an important role in cell signaling. They have shown promise in traversing the BBB, serving dual roles as potential biomarkers for NDs and vehicles for targeted drug delivery. However, the specific mechanisms by which exosome influence NDs are not fully understood, necessitating further investigation into their attributes and functionalities in the context of NDs. This review explores how exosomes mediate multifaceted interactions, particularly in exacerbating pathogenic processes such as oxidative stress, neuronal dysfunction, and apoptosis integral to NDs. It provides a comprehensive analysis of the profound impact of exosomes under stress and disease states, assessing their prospective utility as biomarkers and drug delivery vectors, offering new perspectives for tackling these challenging diseases.